PENGGUNAAN BAHASA INDONESIA DALAM KOMUNIKASI MARKETING DI PERUSAHAAN HONDA PT LUMENINDO GILANG CAHAYA SURABAYA - Laura Geovani Rumahorbo; Sherly Anindhya Meyra L. T; Iola Riris Simanjuntak; Katherine Situmorang; Alifah Naurah Saalsabila; Diandra Dwi Navita; Endang Sholihatin (Jurnal Ilmiah Wahana Pendidikan, 2023)
In indonesian languange marketing communications activities of the company to ensure the language used can strengthen the company's image and increase consumer confidence. This study purpose is to analyze the use of Indonesian in marketing communications at the Honda company PT Lumenindo Gilang Cahaya Surabaya, to find out how to use Indonesian in marketing communications in Honda company PT Lumenindo Gilang Cahaya, and to find out how the strategy is to use Indonesian in marketing communications to attract potential buyers' interest in PT Lumenindo Gilang Cahaya's Honda and how the impact of using non-standard Indonesian in marketing communications has on the image of Honda PT Lumenindo Gilang Cahaya's company. The procedure in this study is a qualitative approach, then data is collected through interviews, observations, and surveys. This study found: 1) the use of Indonesian in marketing communications as a basic aspect of delivering business messages, 2) strategies for using Indonesian in marketing communications to attract potential buyers, using easy-to-understand Indonesian, adjusting the language to target buyers, and using popular terms. 3) the impact of using non-standard Indonesian in marketing communications on company image can make the message difficult to understand and reduce consumer confidence in the company.